발목 관절의 미만형 색소 융모 결절성 활액막염으로 오인된 통풍성 관절염: 증례 보고 - 경민규; Min Gyu Kyung (대한족부족관절학회지, 2025)
Gouty arthritis involving extensive soft tissue deposition around the ankle joint can clinically and radiologically mimic pigmented villonodular synovitis (PVNS). This paper presents the case of a 35-year-old man initially suspected of having diffuse PVNS based on the clinical features such as swelling, pain, and restricted ankle motion, and the magnetic resonance imaging findings suggestive of soft tissue masses and diffuse synovitis around multiple tendons. The patient underwent surgical intervention with a planned extensive synovectomy, the gold standard treatment for diffuse PVNS. The intraoperative examination revealed the widespread deposition of gout tophi rather than hemosiderin-laden tissue, and histopathological analysis confirmed gouty arthritis. Diagnostic uncertainty arose because of mildly elevated serum uric acid levels, along with the absence of typical inflammatory signs such as redness or a heating sensation, and imaging characteristics overlapping with PVNS. This case shows that extensive gouty arthritis may closely mimic diffuse PVNS, highlighting the importance of including tophaceous gout in the differential diagnosis of patients presenting with joint effusion and diffuse synovitis involving the joints and tendons, particularly in the presence of underlying metabolic syndrome risk factors.